2021
DOI: 10.2147/jmdh.s269744
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Antepartum Hemorrhage Among Mothers Who Gave Birth at Suhul General Hospital, 2016: A Case–Control Study

Abstract: Background Antepartum hemorrhage is a very serious problem and contributes significantly to maternal and neonatal morbidity and mortality in developing countries including Ethiopia. Identification of risk factors of antepartum hemorrhage will help for prevention and control programs. Methods An institutional-based case–control study was conducted from July 2013 to June 2016. A simple random sampling technique was employed, and 420 mothers’ medical cards were reviewed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…That is comparable to a study done in Kenyatta Hospital that had the highest level at secondary level for patients with APH (Njoroge, Pinckie L N 2017). Our study finding was also similar to a study done in India that reported cases of APH that were illiterate to be 45.1% (Dibaba B, 2021). From the study, literacy levels are a major determinant of maternal and neonatal outcomes with patients with higher qualifications exhibiting better outcomes for both the control and case groups.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…That is comparable to a study done in Kenyatta Hospital that had the highest level at secondary level for patients with APH (Njoroge, Pinckie L N 2017). Our study finding was also similar to a study done in India that reported cases of APH that were illiterate to be 45.1% (Dibaba B, 2021). From the study, literacy levels are a major determinant of maternal and neonatal outcomes with patients with higher qualifications exhibiting better outcomes for both the control and case groups.…”
Section: Discussionsupporting
confidence: 90%
“…This is opposed to a study done in India that recorded high parity as a risk to APH. (Dibaba B, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Significant evidence reveals [ 15 , 39 , 40 ] that the occurrence of antepartum bleeding results in a decreased blood flow from the mother to the placenta with subsequent hypoxia to the fetus. Studies conducted in Ethiopia have also shown an increased incidence of perinatal asphyxia among mothers who encountered APH [ 15 , 40 ]. This study also identified that antepartum hemorrhage was associated with perinatal asphyxia, consistent with the study conducted in Bangalore, Indonesia [ 41 ], and Accra Ghana [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in India [29], Bangkok Rajavithi hospital [37], Gusau Nigeria [38], and Tigray Ethiopia [23] are in line with this data. Significant evidence reveals [15,39,40] that the occurrence of antepartum bleeding results in a decreased blood flow from the mother to the placenta with subsequent hypoxia to the fetus. Studies conducted in Ethiopia have also shown an increased incidence of perinatal asphyxia among mothers who encountered APH [15,40].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation